PENGARUH PENGGUNAAN BOKIR DALAM MENGOPTIMALKAN RESPIRATORY RATE PADA TB PARU: THE EFFECT OF USING BOKIR IN OPTIMIZING RESPIRATORY RATE IN PULMONARY TUBERCULOSIS - Irma; Rido, Yunihastin P.; Boba, Chiesa G.R.; Elsinta A. Pajanging; Yuniati Tamo Ina; Santoso, Shelfi Dwi Retnani Putri (LPPM STIKes Bahrul Ulum Jombang, 2023)
Pulmonary TB is a disease caused by bacteria that ranks second as the leading cause of death worldwide. One of the issues faced by patients is shortness of breath, characterized by disturbances in respiratory rate. This study aims to determine the effect of using BOKIR in optimizing the respiratory rate in pulmonary TB. The design used is a quasi-experimental design with a one-group pre and post-test with a control group design. The sample used consisted of 40 respondents, divided into two groups, with 20 respondents each for the control and intervention groups, selected using convenience sampling. The intervention provided was PLB using the BOKIR method following Standard Operational Procedures, and RR calculation using observation. Data analysis used the t-test. The results obtained were p=0.251 in the treatment group and p=0.353 in the control group, meaning that this intervention does not have a significant effect. Further research can be conducted using the same method, but researchers may consider adding an estimation of the intervention time.